Pengaruh Dana Perimbangan dan Sisa Lebih Pembiayaan Anggaran Terhadap Belanja Modal Kabupaten/Kota di Provinsi Bangka Belitung - Bella Rahma Sary; Kartika Rachma Sari; Sandrayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of the Balancing Fund and Budget Surplus (SILPA) on Capital Expenditure in regency/municipal governments of the Bangka Belitung Province during the 2019–2023 period. The research method used is quantitative with an associative approach. The data used are secondary data sourced from audited budget realization reports obtained from the official websites of DJPK and BPK RI. The analysis technique employed is multiple linear regression using SPSS version 26. The results show that partially, the Balancing Fund does not have a significant effect on Capital Expenditure, while SILPA has a positive and significant effect. Simultaneously, the Balancing Fund and SILPA significantly influence Capital Expenditure. The Adjusted R Square value of 0.227 indicates that 22.7% of the variation in Capital Expenditure can be explained by the Balancing Fund and SILPA, while the rest is influenced by other factors outside the model. These findings imply that effective planning and management of SILPA can encourage an increase in regional capital expenditure.